Atlas of African agriculture research and development: Revealing agriculture's place in Africa - Sebastian, Kate (International Food Policy Research Institute, 2014)
The Atlas of African Agriculture Research & Development is a multifaceted resource that highlights the ubiquitous nature of smallholder agriculture in Africa; the many factors shaping the location, nature, and performance of agricultural enterprises; and the strong interdependencies among farming, natural resource stocks and flows, rural infrastructure, and the well-being of the poor.